Effect of Ulinastatin Combined with Xingnaojing Injection on Severe Traumatic Craniocerebral Injury and Its Influence on Oxidative Stress Response and Inflammatory Response. (10th January 2022) - An, Zexin; Yin, Yong; Zhang, Lei; Wang, Bo; Cui, Tao; Li, Meng; Zhuo, Jianwei; Zhang, Jing; Wang, Kai; Zhang, Wenwen; Ji, Meng; Sun, Jilin; et al.
Abstract : Objective . This study is aimed at exploring the effect of ulinastatin combined with Xingnaojing injection on severe traumatic craniocerebral injury and its influence on oxidative stress response and inflammatory response in patients. Methods . A total of 100 patients with severe traumatic craniocerebral injury admitted to our hospital from January 2018 to January 2020 were selected and equally assigned into a study group (50 cases) and a control group (50 cases) according to a random sampling method. Patients in study group received treatment of ulinastatin combined with Xingnaojing injection, while those in control group were treated with ulinastatin only. The study compared the two groups on the oxidative stress response, inflammatory response, the therapeutic effect, and the incidence rate of adverse reactions. Results . It is observed that patients in study group obtained lower levels of free cortisol (FC) and norepinephrine (NE) in the serum and higher level of total thyroxine (TT4) after treatment compared with those in control group with significant difference (P < 0.05 ); in the meantime, they were examined to have significantly fewer oxidative stress response products, lower serum inflammatory factor level, and serum indicator levels of craniocerebral injury as opposed to those in control group, suggesting significant differences (P < 0.05 ); study group demonstrated higher treatment response rate and lower incidence rate of adverse reactions compared with control group with a significant difference (P < 0.05 ). Conclusion . The study found that ulinastatin combined with Xingnaojing infection has a significant effect in the treatment of severe traumatic craniocerebral injury, which can reduce the degree of craniocerebral injury and the level of inflammatory factors in the serum of patients. It is worthy of being promoted and applied clinically.